Assessing the Effectiveness of Prophetic Leadership-Based Basic Leadership Training among Tenth-Grade Female Students: A Pretest–Posttest Approach - Ismala Astari (CV. Era Digital Nusantara, 2026)
Leadership is an important skill that needs to be instilled from adolescence, especially in Islamic boarding schools. This study aims to describe the impact of profit-based leadership training on improving the understanding of leadership materials in 10th-grade female students. The method used is a quantitative descriptive approach with a pre-test and post-test design on training materials covering self-leadership, communication, conflict management, and decision-making. The research subjects consisted of 30 female students selected through a purposive sampling technique. The pre-test results showed that the participants' initial level of understanding was still in the low to moderate category. After participating in a series of training sessions during the four sessions, the post-test results showed a significant increase in mastery of concepts and application of leadership materials. Descriptive analysis showed that some participants experienced an increase in scores of more than 30% compared to their initial scores. These results indicate that profit leadership training can be a relevant and effective strategy in improving the knowledge and readiness of female students in carrying out the leadership role of 10th-grade female students in an Islamic boarding school environment.